(untitled) (Journal of the Pakistan Medical Association, 2020)
Abstract People who inject drugs (PWIDs) reuse injection equipment and other paraphernalia, which is a major source of transmission of human immunodeficiency (HIV) and hepatitis C virus (HCV) infections. PWIDs who use infected injections develop many surgical complications which are life- threatening. The most common complication is infected pseudoaneurysm. To assess complications requiring surgery in drug abusers, a study was conducted in the East Surgical Ward of Mayo Hospital Lahore, Pakistan from Jan 2017 to Jan 2019. A total of 48 PWIDs presented to the surgical department, out of which 39 (81%) were HIV positive, and 31 (64%) were HCV positive. Of the 52% who had pseudoaneurysm, 92% had femoral and popliteal aneurysm and 8% had brachial aneurysm. After ligation and excision of pseudoaneurysm only 8% required major amputation. Mortality rate was 0%. Ligation and excision is a safe option in pseudoaneurysm. Continuous...